Relationship between the level of family support in the care and quality of life of patients with type 2 diabetes mellitus treated at the outpatient clinic of the Guillermo Almenara Irigoyen National Hospital, Lima, Peru - Chávez Zegarra, Gaby Sonia (2019)
Objective: To determine the relationship between the level of family support in the care and quality of life ofpatients with type 2 diabetes treated at the Outpatient Service of Endocrinology HNGAI. Methodology: Thestudy was non-experimental quantitative correlational design of cross- cutting using a sample of 142 patientsdiagnosed with type 2 diabetes. To collect data consolidated two instruments were applied in a single document,to measure the quality of life of the individual SF Health Questionnaire was used - 36 and the MOS SocialSupport Questionnaire to measure perceived level of family support. Statistical applied were descriptive and toestablish the correlation Pearson r was used whereas correlate variables are categorical type. Results: We foundthat most patients with type 2 diabetes has a quality of life regularly (35.2%) to poor (30.28%), has good familysupport (35.9%) to excellent (22.5%), and finally the quality of life according to the level of family support isgood (51.3%), so it is determined that the family support positively influences the quality of life of patientswith type 2 diabetes. Conclusion: There is a relationship between quality of life and family support, except inthe physical dimension and transmission of health that are unrelated to family support in patients with Type 2Diabetes Mellitus activity